A review on biomass gasification syngas cleanup. (1st October 2015) - Abdoulmoumine, Nourredine; Adhikari, Sushil; Kulkarni, Avanti; Chattanathan, Shyamsundar
Highlights: The study reviews biomass syngas cleanup technologies and R&D status. In-depth synthesis of gas cleanup to remove major syngas contaminants is provided. Contaminants of focus are tar, NH3, HCN, H2 S, COS, halides (HCl) and trace metals. Major technical barriers related to gas cleanup are discussed. Abstract: Energy, fuel and chemical production from biomass is increasingly attracting interest in the world. Gasification of biomass can produce raw syngas which contains CO, CO2, H2 and CH4 . In addition, raw syngas contains minor but significant quantities of undesirable impurities – collectively known as syngas contaminants. Syngas contaminants are composed of tars, nitrogen based compounds (NH3, HCN, etc.), sulfur based compounds (H2 S, COS, etc.), hydrogen halides (HCl, HF, etc.) and trace metals (Na, K, etc.). Raw syngas cleanup is an essential step prior to syngas utilization in downstream applications. In recent years, significant research attention has been devoted to syngas cleanup to reduce contaminants below tolerable limits. The present paper is a comprehensive review of cold gas and hot gas syngas cleanup for major contaminants in syngas (tar, NH3, H2 S, HCl and trace metals). This review organizes and discusses investigations on syngas for all major contaminants, critically reviews important challenges in syngas cleanup and discusses recent advancements in hot and cold gas cleanup.